The Thin Green Line An Assessment of DoD's Readiness and Environmental Protection Initiative to Buffer Installation Encroachment - Lachman, Beth E. (RAND Corporation, 2007)
This monograph assesses the effectiveness of DoD's Readiness and Environmental Protection Initiative to help testing and training installations deal with encroachment from sprawl and other sources. The authors identify the main causes of encroachment; detail the benefits, both to the military and local communities, of buffering areas near installations with REPI projects; and provide recommendations for how to improve REPI's effectiveness.